Common and Separate Ownership of Projects - Axel Gautier (University of Bonn, Bonn Graduate School of Economics (BGSE), 2002)
This note points out the differences between conducting several projects within one big firm (common ownership) and conducting each project within an independent firm (separate ownership).
Keywords: D23; L22; G31; G32; 330; Conglomerate; Nature of the firm; Market Vs hierarchies